Thinking about the end of life when it is near: a comparison of German and Portuguese centenarians - Boerner, Kathrin; Rott, Christoph (Research on aging, 2019)
This study examined how common thinking of and planning for the end of life (EOL) is among German and Portuguese centenarians, and whether patterns of EOL views are shaped by cultural and individual characteristics. A significant portion of centenarians in both countries reported not thinking about the EOL, not believing in the afterlife, and not having made EOL arrangements. Latent class analysis identified three EOL patterns: Class 1 (EOL thoughts with EOL arrangements and afterlife beliefs), Class 2 (EOL arrangements and afterlife beliefs without EOL thoughts), and Class 3 (Overall low endorsement of EOL items). The proportion of Portuguese centenarians was higher in Class 1 and of German centenarians higher in Classes 2 and 3. Centenarians’ demographic, social, and health characteristics were significantly different across EOL patterns. As lack of EOL planning can result in poor EOL quality, enhancing communication among centenarians, family, and health-care professionals seems imperative.
First Published October 28, 2018
Gesehen am 14.02.2019